Impact of Mobile Banking on Customer Satisfaction - Panthi, Rishikesh; Poudel, Shiva Raj; Dahal, Sanjita; Dahal, Subhadra; Sangaurala, Tanka (Journal of Durgalaxmi, 2024)
This research aims to examine the impact of different dimensions of mobile banking services on customer satisfaction. For this, the primary data have been collected through a set of structured questionnaires directly from 120 bank customers who currently used mobile banking services. A well-structured close-ended questionnaire was designed and distributed through face-to-face interaction with bank customers who used mobile banking facilities. The measures used five scales Likert type data with the response option from 1 = strongly disagree to 5 = strongly agree. The data analysis tools used for the study were descriptive statistics and regression analysis. The conclusion drawn from the study is mobile banking service quality has a significant positive impact on customer satisfaction in the context of Nepal. The study found that reliability, responsiveness, accessibility, convenience, and security attributes of mobile banking applications have a significant positive impact on customer satisfaction. Therefore, the policymakers and the executives of the commercial banks should focus on these attributes of mobile banking services in order to retain the customer's loyalty toward the banking services.